ECUADOR AFTER THE COMMODITIES BOOM: A RENTIER SOCIETY’S LABYRINTH - Alarcon, Pedro; Peters, Stefan (Cadernos do CEAS: Revista crítica de humanidades, 2020)
After failing to renegotiate debt conditions with China, Lenín Moreno’s government reverted to traditional international financial measures in a further attempt to cover the fiscal deficit left by the dramatic drop in oil prices of 2014. In order to meet targets agreed with lenders, Moreno scrapped subsidies on transportation fuels by the beginning of October 2019. However, amid nationwide protests, Moreno repealed the measure after nearly two weeks. Interpretations of the protests have been manifold; this paper presents a further reading based on rentier theory, and argues that a significant source of opposition to the elimination of subsidies is to be found in peoples’ claim on their portion of oil rent, the expression of a quasi-naturalized right derived from living in a natural resources-rich country.